Seismic behavior of multistoried buildings with soft intermediate storey - Azam, Shaik Kamal Mohammed; Hosur, Vinod (Journal of Structural Engineering, 2024)
The vulnerability of multistoried buildings due to the presence of soft stories is addressed in the seismic design standards of many countries. In this paper, the aspect of difference in performance of the building with a soft storey under seismic forces, specifically, for different positions of the soft storey along the height of the building structure is presented. Since the stiffness contribution of masonry infill in the lower stories is large compared to the stiffness contribution of the upper stories, the effect of positioning of the soft storey along the height of the building structure is significant. The soft storey located in the lower part of the multistoried building especially the first storey is very undesirable as it attracts severely large seismic forces. At the same time, the soft storey located in the upper part of the multistoried building especially the top storey does not significantly affect the performance compared to the performance of the fully infill frame. This aspect needs consideration in the proposal for amplifi cation factor for the forces in the design of weak/softstoreyframe members in different national codes.